1980
DOI: 10.1128/jcm.11.6.604-609.1980
|View full text |Cite
|
Sign up to set email alerts
|

Cultural and physiological characteristics and antimicrobial susceptibility of Clostridium botulinum isolates from foodborne and infant botulism cases

Abstract: Isolates Clostridium botulinum from foodborne and infant botulism cases in the United States were compared on the basis of toxigenicity, cultural and biochemical characteristics, metabolic products, and susceptibility to antimicrobial agents. Seventy-eight strains, including 42 from foodborne and 36 from infant botulism sources, were examined. Cultures on anaerobic blood agar exhibited circular, spindle, and rhizoid (medusa head) colonies. Overall, the characteristics of isolates from foodborne and infant botu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
1

Year Published

1981
1981
2010
2010

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 9 publications
1
27
1
Order By: Relevance
“…The antigenicities of the toxin were different between the two groups; that of the toxic component partially, while that of the nontoxic component entirely, as the nontoxic component formed no precipitation line to heterologous antitoxin [1]. In the biochemical tests, there was no difference between the two groups as reported by Dezfurian et al [13].…”
Section: Discussionmentioning
confidence: 94%
“…The antigenicities of the toxin were different between the two groups; that of the toxic component partially, while that of the nontoxic component entirely, as the nontoxic component formed no precipitation line to heterologous antitoxin [1]. In the biochemical tests, there was no difference between the two groups as reported by Dezfurian et al [13].…”
Section: Discussionmentioning
confidence: 94%
“…The medium is similar to EYA but contains cycloserine, sulfamethoxazole, and trimethoprim. The antimicrobial agents inhibit the majority of microorganisms present in the feces but do not inhibit group I C. botulinum (toxin types A, B, and F), which includes the types involved in infant botulism (1). This group of C. botulinum grows on CBI and exhibits lipase activity.…”
mentioning
confidence: 99%
“…Production of botulinal toxin alone by a lipase-positive organism was considered sufficient for identifying an isolate as C. botulinum. Complete characterization of the organisms isolated in the original laboratory examination showed that they were typical of proteolytic strains of C. botulinum (1).…”
mentioning
confidence: 99%
“…Once the symptoms of botulism appeared in mice, neither treatment was helpful. Metronidazole was selected for this study because of its unique bactericidal activity against anaerobic bacteria (13), because of in vitro studies showing that C. botulinum is highly sensitive to metronidazole (5,15), and because of a previous study showing the unique efficacy of metronidazole as compared with alternative drugs for the delayed treatment of infections involving Bacteroidesfragilis (1). The utility of antimicrobial agents in treating patients with wound botulism is unclear (10,12).…”
mentioning
confidence: 99%